Arthropod pests of Coconut, Cocos nucifera L. and their Management - Seni, Atanu (International Journal of Environment, Agriculture and Biotechnology, 2019)
Coconut, Cocus nucifera L. (Palmaceae) is an important crop and widely cultivated in the tropical and subtropical regions of the world. Millions of people depend on this crop by employed in various coconut-based industries like coconut oil, dry coconut powder, tender coconut, coir, coconut cake, etc. But its production has been greatly affected by the infestation of several arthropod pests. Among them; Rhynchophorus ferrugineus Olivier, Oryctes rhinoceros L, Opisina arenosella Walker, Aceria guerreronis Keifer, Latoia lepida (Cramer) and Aspidiotus destructor Signoret are causing maximum damage in coconut which ultimately affect the true potential of the crop. Here, the present article provides recent information regarding different arthropod pests of coconut, their identification, life-history, nature of damage and their management in an effective way.